2007
DOI: 10.1136/thx.2006.071290
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bronchodilator responsiveness in preschool children using forced oscillations

Abstract: Background: The forced oscillation technique (FOT) requires minimal patient cooperation and is feasible in preschool children. Few data exist on respiratory function changes measured using FOT following inhaled bronchodilators (BD) in healthy young children, limiting the clinical applications of BD testing in this age group. A study was undertaken to determine the most appropriate method of quantifying BD responses using FOT in healthy young children and those with common respiratory conditions including cysti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
104
3
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(129 citation statements)
references
References 24 publications
19
104
3
3
Order By: Relevance
“…In the present study, we assessed BDR using R rs and X rs at 8 Hz as these were previously recommended by Thamrin et al 10 Our data onfirm their earlier data that the change in both R rs and X rs following bronchodilator was related to the magnitude of the baseline values. In our study, we have found a correlation between BDR expressed as a percent of baseline and height for R rs8 .…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…In the present study, we assessed BDR using R rs and X rs at 8 Hz as these were previously recommended by Thamrin et al 10 Our data onfirm their earlier data that the change in both R rs and X rs following bronchodilator was related to the magnitude of the baseline values. In our study, we have found a correlation between BDR expressed as a percent of baseline and height for R rs8 .…”
Section: Discussionsupporting
confidence: 68%
“…This finding is similar to that reported by the Australian group. 18 The major difference between our study and the one from Thamrin et al 10 is the use of 600 mg of salbutamol to assess BDR whereas 200 mg was used in the present study. Despite this difference, the change in both R rs8 and X rs8 Pediatric Pulmonology Fig.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Measurements of PEF on a day-to-day basis may allow monitoring of the variable airway obstruction, which is considered one of the key features of asthma and the variability in PEF may be predictive of exacerbations [16,32]. The mean day-to-day variability of peak flow in healthy children is between 6.2% and 8.2%, with a 95th percentile of 12.3-31% [33,34].…”
Section: Measurement Of Peak Flowmentioning
confidence: 99%